2005
DOI: 10.1111/j.0022-202x.2005.23824.x
|View full text |Cite
|
Sign up to set email alerts
|

Solar-Simulated Ultraviolet Radiation Induces Abnormal Maturation and Defective Chemotaxis of Dendritic Cells

Abstract: Exposure to ultraviolet (UV) light induces immunosuppression. Different evidences indicate that this phenomenon is mainly a consequence of the effect of UV light on skin dendritic cells (DC). To investigate the cellular and molecular basis of this type of immunosuppression, we assessed in vitro the effect of solar-simulated UV radiation on the phenotypic and functional characteristics of human monocyte-derived DC and Langerhans-like DC. UV radiation induced a decreased expression of molecules involved in antig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 35 publications
4
18
0
Order By: Relevance
“…A 10–15% cytotoxicity was induced at 4 J/cm 2 (UV induced apoptosis, see Timares et al [21]). This is similar to the results published by Mittelbrunn et al [22] who reported a partial maturation of PDMDCs and approx. 33% cytotoxicity after irradiation with 5 J/cm 2 UVA and 0.4 J/cm 2 UVB generated by a xenon solar simulator.…”
Section: Discussionsupporting
confidence: 92%
“…A 10–15% cytotoxicity was induced at 4 J/cm 2 (UV induced apoptosis, see Timares et al [21]). This is similar to the results published by Mittelbrunn et al [22] who reported a partial maturation of PDMDCs and approx. 33% cytotoxicity after irradiation with 5 J/cm 2 UVA and 0.4 J/cm 2 UVB generated by a xenon solar simulator.…”
Section: Discussionsupporting
confidence: 92%
“…Human monocyte-derived DCs were purified from buffy coats obtained from 3 healthy donors and irradiated with 3.7 J/cm 2 UVA+0.3 J/cm 2 UVB, using a solar simulator. This irradiation dose induces the secretion of TNF-alpha and modifies the expression of several DC surface receptors without causing significant hypodiploidy [14]. Statistical analyses of gene expression values of non-irradiated versus irradiated DC, revealed the modulation of 64 annotated genes with p<0.05.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, several groups have reported the effect of solar-simulated UV radiation on the phenotype and function of human monocyte-derived DCs. Solar-simulated UV radiation results in defective DC maturation and an anomalous migratory phenotype [11], [14]. However, gene expression changes induced in DCs in response to UVA/UVB exposure have not been systematically examined.…”
Section: Introductionmentioning
confidence: 99%
“…When high dose of UV was irradiated (as used in this study), apoptosis or cell damage instead of maturation was induced on skin dendritic cells [4,28,29]. Using Western-blotting analysis and the experiments using a specific inhibitor for p38 MAPK, it is clarified that apoptosis of MoDC is mediated at least partly by p38 MAPK [4].…”
Section: Discussionmentioning
confidence: 91%